Quantification of T-cell Migration in Confined and 3D Conditions - Zhang Zhou, Jack; Movilla Meno, Nieves; Oñate Salafranca, Carmen; Guerrero Barrado, Pedro Enrique; Pardo Jimeno, Julián; García Aznar, José Manuel (Jornada de Jóvenes Investigadores del I3A, 2023)
Migration is one of the immune system’s fundamental processes in order to carry out its function of defense against pathogens and aberrant cells. Therefore, a novel microfluidic-based approach was adopted to comprehend the immune response. We found that T lymphocytes show higher velocity under confinement in comparison to 3D migration.